Training Pediatricians to Address Health Disparities: An Innovative Residency Track Combining Global Health With Community Pediatrics and Advocacy. (September 2018) - Pak-Gorstein, Suzinne; Batra, Maneesh; Johnston, Brian; Grow, H. Mollie; Grant, Abigail; Shugerman, Richard; Lago, Sylvia; Stapleton, F. Bruder; McPhillips, Heather
Abstract : Problem: Pediatric residency programs have been tasked to train a workforce of pediatricians with skills in community pediatrics (CP) and advocacy, and knowledge of global child health priorities. Approach: In 2009, the University of Washington (UW) Seattle Children's Hospital pediatric residency program developed the Resident Education in Advocacy and Child Health (REACH) program, a combined pathway for global health (GH) and CP training. After participating in a combined curriculum, residents complete a community immersion either in Kisii, Kenya (GH) or rural Washington (CP). This approach provides an efficient use of faculty and administrative resources and delivers a sustainable and ethical strategy for inspiring pediatric residents to address child health problems at a systems level. Outcomes: Between 2009 and 2013, the percentage of graduating residents from the UW pediatric residency program who rated GH training as "outstanding/excellent/good" increased from 58.4% to 100%, and the percentage rating community and population health training as "outstanding/excellent/good" increased from 56% to 88.8%. Annual applicant surveys in the period 2011–2014 revealed that the REACH program led a significant percentage of candidates to rank the UW pediatric residency more favorably because of its GH (37%–48%) and CP (55%–74%) training. Next Steps: A mixed-methods assessment will evaluate the impact on resident confidence in core areas of community health and advocacy including collaborating with community groups, setting professional career goals, addressing underlying determinants of health during patient encounters, communicating in cross-cultural settings, and advocating for child health. A survey will assess outcomes on graduates' careers.